Analysis of Calculation, Withholding, and Deposit of Income Tax Article 21 on The Salary of Perum Perhutani Employees KPH Sukabumi: English - Maulida, Silvia; Nurodin, Idang; Tanjung, Hendra (Muhasabatuna : Jurnal Akuntansi Syariah, 2023)
This research, is a qualitative research that aims to find out how the calculation, withholding, and deposit of Article 21 Income Tax on the salaries of employees of Perum Perhutani KPH Sukabumi by comparing research data with Law number 36 of 2008 concerning the fourth amendment to law number 7 of 1983 concerning Income Tax, and Law number 7 of 2021 concerning harmonization of tax regulations using observation, documentation, interview and triangulation data collection techniques. The results of this study indicate that the calculations and deductions are in accordance with Law number 36 of 2008 concerning the fourth amendment to law number 7 of 1983 concerning Income Tax, and Law number 7 of 2021 concerning harmonization of tax regulations, then on deposit KPH Sukabumi is in compliance and knows that tax payments must be made before the 10th of the following month after the end of the tax period, but KPH Sukabumi was late in paying taxes several times which resulted in a bill in the form of an administrative fine of 2% which must be received by KPH Sukabumi which will be paid on end of year.